2005
DOI: 10.1093/schbul/sbj064
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Recovery Outcomes for Clients With Co-Occurring Schizophrenia and Substance Use Disorders

Abstract: The long-term courses of people with schizophrenia and of those with substance use disorder have been studied separately and extensively. The long-term course of clients with co-occurring schizophrenic and substance use disorders has, however, not been examined. This article reports 10-year outcomes for 130 clients with co-occurring schizophrenic and substance use disorders in the New Hampshire Dual Diagnosis Study. In addition, we report on 6 "recovery outcomes," identified by dual diagnosis clients, as examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 49 publications
5
82
0
Order By: Relevance
“…The term recovery as such has different meanings [12] but abstinence is a common point for all of these researches [13]. Exploring the relationship that Jung accounted in his correspondence with Bill [1], many authors have suggested spirituality as an important motivator for recovery in substance-dependent people [14,15], and it is a concept that operates in a twelve-step recovery process [16,17,18,[19][20][21]22].…”
Section: Relevant Findings On Spirituality and Its Importance For Recmentioning
confidence: 99%
“…The term recovery as such has different meanings [12] but abstinence is a common point for all of these researches [13]. Exploring the relationship that Jung accounted in his correspondence with Bill [1], many authors have suggested spirituality as an important motivator for recovery in substance-dependent people [14,15], and it is a concept that operates in a twelve-step recovery process [16,17,18,[19][20][21]22].…”
Section: Relevant Findings On Spirituality and Its Importance For Recmentioning
confidence: 99%
“…60 This approach integrates more of the elements of service user-defined recovery such as a range of life domains and individual values. 61 Measures such as the Global Assessment of Functioning (GAF 62 ) scale and the Quality of Life Scale 63 are commonly used. Research studies often use these measures alongside the more traditional symptom and relapse measures.…”
Section: Introductionmentioning
confidence: 99%
“…Research from different treatment settings indicate that 30 per cent of those with less severe mental illness and heavy substance use attain sustained remission [22], whereas up to 60 per cent of those with SMI and less severe substance use attain sustained remission [23,24].…”
Section: Introductionmentioning
confidence: 99%